1981
DOI: 10.1159/000137543
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Triamterene and Its Phase I and Phase II Metabolites on Sodium Transport of the Isolated Frog Skin

Abstract: We studied the effects of triamterene (TA) and its phase I and phase II metabolites, p-hydroxytriamterene (OH-TA) and p-hydroxytriamterene sulfuric acid ester (OH-TA ester), on sodium transport in the isolated frog skin. While TA applied to the inside (corial side) surface had no effects on potential difference (PD) and short-circuit current (SCC), TA, OH-TA, and OH-TA ester at a concentration of 10–5 mol/l significantly decreased SCC by 19, 24 and 16%, respectively, when added to the solution bathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Amiloride is not subjected to endogenous metabolism (WEISS et al 1969), whereas triamterene, after its intestinal absorption, is rapidly and extensively metabolised to p-hydroxytriamterene and p-hydroxytriamterene sulfate ester (LEHMANN 1965), which are at least as potent as the parent compound (GREBIAN et al 1978;KRAMER et al 1981). Triamterene is excreted as p-hydroxytriamterene sulfate (LEHMANN 1965).…”
Section: Metabolism and Biotransformationmentioning
confidence: 99%
“…Amiloride is not subjected to endogenous metabolism (WEISS et al 1969), whereas triamterene, after its intestinal absorption, is rapidly and extensively metabolised to p-hydroxytriamterene and p-hydroxytriamterene sulfate ester (LEHMANN 1965), which are at least as potent as the parent compound (GREBIAN et al 1978;KRAMER et al 1981). Triamterene is excreted as p-hydroxytriamterene sulfate (LEHMANN 1965).…”
Section: Metabolism and Biotransformationmentioning
confidence: 99%
“…TA inhibits passive sodium transport from the luminal side of transporting epithelia [25][26][27], resulting in im paired movement of potassium from cell to lumen, since the latter is functionally coupled to sodium movement. Although initial studies suggested that these events in volved inhibition of aldosterone [I], subsequent investi gations have clearly demonstrated that TA can produce these effects either when aldosterone is physiologically suppressed [28] or when it is completely absent as occurs following adrenalectomy [29].…”
Section: Pharmacodynamicsmentioning
confidence: 99%